Medial Position and Counterclockwise Rotation of the Parietal Scalp Hair-Whorl as a Possible Indicator for Non-Right-Handedness - Heinrich Schmidt; Martin Depner; Michael Kabesch (The Scientific World Journal)
The objective of our study was to assess the association between position and swirling direction of the parietal whorl (PW) and handedness. In 519 patients of a pediatric practice, PWs were located and the swirling direction determined. Of those patients, handedness could be specified in 217. The right-sided PW (n = 347; 70.8%) and the clockwise (CW) swirling type (n = 411; 83.9%) of all participants were predominant in children with one PW. Non-right-handedness (NRH) was found in 40 (18.4%). Medial position of the whorl per se increases the chance for NRH, indifferent of the swirling direction. In patients with counterclockwise (CCW) swirling, the chance of NRH increased 3.5-fold for the right-sided, 5.4-fold for the left-sided, and 12.9-fold for the medial-positioned whorl. We conclude that NRH is associated with the position (medial!) and the swirling direction (CCW!) of the PW.